Design, Simulation, and Performance of Afsrg 8/8 in an Electric Power Generation System with Low Speed Drive - Rafles Prasuki Pasaribu; Parlin Siagian; Rahmaniar Rahmaniar (Jurnal Info Sains : Informatika dan Sains, 2026)
Low-speed micro-hydro power plants require generators with high starting torque, good efficiency, and the ability to operate at low rotational speeds. This study designs and builds an Axial Flux Switched Reluctance Generator (AFSRG) with an 8/8 configuration to address those needs. AFSRG was chosen for its simple structure, robustness, and magnet-free operation. The methodology included geometric design using CAD software, electromagnetic simulation using FEMM, and experimental testing in a micro-hydro setup. The results show that the 8/8 AFSRG can generate 48V at 300 rpm with a system efficiency of 78%. AFSRG is feasible for use in remote micro-hydro power generation applications with low-speed water flow.